Boosting academic engagement through soft skills: the mediation of positive emotions and life satisfaction - Wang, Xiaoling; Wan Jaafar, Wan Marzuki; Sulong, Rose Manisah (SAGE Publications, 2025)
In recent years, soft skills have gained growing attention as key factors influencing students’ academic performance and psychological well-being. This study investigates the extent to which soft skills are associated with undergraduate students’ engagement, and whether this relationship is mediated by positive emotional experiences and overall life satisfaction. The research involved 335 undergraduates enrolled at four universities located in South-Sichuan, China. Participants completed four validated online self-report instruments designed to assess their levels of soft skills, positive affect, life satisfaction, and engagement. Analyses revealed that soft skills exert a significantly positive effect on students’ positive emotions, life satisfaction, and engagement. Moreover, both positive emotions and life satisfaction served as partial mediators in the link between soft skills and engagement, emphasizing their intermediary role in fostering greater academic performance. This research contributes to the limited body of empirical studies examining the influence of soft skills on university students’ academic behaviors within the Chinese higher education context. The results underscore the dual value of soft skills in promoting psychological well-being and enhancing academic commitment. Additionally, the findings provide empirical support for the Broaden-and-Build Theory, suggesting that soft skills function as foundational assets that nurture both personal growth and educational achievement.